Monuments between covers: the politics of textbooks - Tyack, David (1999)
History textbooks have represented state-approved civic truth. They reveal what adults thought children should learn about the past and are probably the best index of what young Americans did learn in class. History texts have given the past a patriotic gloss, varnishing familiar icons and perpetuating familiar interpretations. Like monuments designed to commemorate and re-present emblematic figures and events, textbooks shaped the public culture. But over time, textbooks did change, for many groups insisted that their truths prevail. Conflicts often intensified in periods of stress - hot and cold wars, depression, and sharp demographic shifts - when loyalty police went on alert and social activists recruited allies. The present history wars are a late chapter in a long book. - Reproduced
Keywords: Textbooks